The problem of space and time in moderen Kazakh falsafes (Journal of Philosophy, Culture and Political Science, 2025)
The notions of space and time are thoroughly examined in the framework of Kazakh philosophy in this article. By fusing conventional wisdom with contemporary philosophical developments, the study seeks to offer a fresh interpretation of these core ideas in the context of Kazakhstan's distinct historical and cultural legacy. The main purpose of the research is to deeply analyze and comprehend these concepts in Kazakh philosophy, as well as to identify ways to interpret and rethink them in the context of cultural and historical features of the country.The research includes a variety of methods such as historical and philosophical analysis, comparative approach, cultural context analysis, interdisciplinary research and phenomenological analysis. The article examines in detail the influence of Kazakh culture and history on the understanding and interpretation of space and time, emphasizing the unique combination of nomadic traditions and modern influences. Special attention is paid to the results of a survey conducted among the public, the purpose of which was to collect opinions and views on the issue from various perspectives. The survey included questions related to the associations of the concepts of "space" and "time", and allowed us to identify how these concepts are perceived in modern Kazakh society.Key words: time, space, cultural factors, Kazakh falsehood, philosophical traditions.